Gaya Kepemimpinan Gembala Dan Kerinduan Melayani Dengan Pertumbuhan Jemaat - Hariyanto Hariyanto (Sekola Tinggi Teologi Sangkakala Jakarta, 2020)
This research aims to find out how big is the relationship between the opinions of young people about the pastoral leadership style and the desire to serve with church growth. The research was executed in Gereja Kristen Sangkakala Indonesia Indonesia Jemaat Betlehem Grogol Permai, DKI Jakarta. The results of the data analysis state that, first: